Tracking of cellular atypes of the cut of uterus of women in Primary Care - Jamile Mika Yoshikawa Kurebayashi; Márcia Barbieri; Maria Cristina Gabrielloni (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to analyze the screening for cervical cell atypias in women assisted in Primary Care. Methods: quantitative, retrospective and cross-sectional study, with analysis of 190 medical records of women who had atypical results from the cervical cytopathological exam collection from 2012 to 2014. Results: the most frequent atypias found were possibly Non-neoplastic squamous (ASC-US, 57.4%) and Low-grade intraepithelial lesion (LSIL, 23.2%). The time elapsed between the exam and the result was 24 days. The professional's conduct after the result of the last cervical cytopathology was adequate for 51.1% of women. Conclusions: there is a need to improve the cervical cancer screening program and correctly target the atypia identified, aiming at the access of the target population for the diagnostic investigation and treatment of precursor lesions of cervical cancer.